Contributions of childhood adversities to chronic pain among mid-life employees. Issue 3 (May 2022) - Salonsalmi, Aino; Pietiläinen, Olli; Lahelma, Eero; Rahkonen, Ossi; Lallukka, Tea
Aims: Chronic pain is a notable burden on public health, with past and present factors contributing to it. This study aimed to examine the associations between childhood adversities and chronic pain. Methods: Data on seven childhood adversities, chronic pain and disabling pain were derived from questionnaire surveys conducted in 2000, 2001 and 2002 among 40- to 60-year-old employees (response rate of 67%) of the City of Helsinki, Finland. The study included 8140 employees (80% women). Logistic regression was used in the analyses, and the results are presented as odds ratios (OR) and their 95% confidence intervals (CI). Age, sex, the father's education, the participant's education, marital status, working conditions, sleep problems and common mental disorders were included as covariates. Results: In the age-adjusted models, childhood economic difficulties (OR=1.60, 95% CI 1.41–1.81), childhood illness (OR=1.74, 95% CI 1.45–2.08), parental divorce (OR=1.26, 95% CI 1.07–1.48), parental alcohol problems (OR=1.34, 95% CI 1.18–1.52) and bullying at school or among peers (OR=1.59, 95% CI 1.37–1.89) were associated with chronic pain. Working conditions, sleep problems and common mental disorders each slightly attenuated the associations between childhood adversities and chronic pain. Childhood economic difficulties among women (OR=1.72, 95% CI 1.40–2.10), childhood illness (OR=1.40, 95% CI 1.07–1.82) and bullying at school or by peers (OR=1.91 95% CI 1.48–2.46) were also associated with disabling pain. Conclusions: Childhood adversities were associated with chronic pain in mid-life, and the associations mainly remained after adjustments. Investing in the well-being of children might prevent pain and promote well-being in mid-life.